â€œâ€œPENERAPAN MATERIAL REQUIREMENT PLANNING PADA PERSEDIAAN BAHAN BAKU DAN PENGARUHNYA TERHADAPâ€EFISIENSI BIAYA PERSEDIAAN (Survei pada Roti Ganep Solo) - Rahayuning Citro, Kesya Indrika; Suseno, Y. Djoko; Sunarso, Sunarso (Universitas Slamet Riyadi, 2018)
Ganep Bakery Solo is a company of food in the form of snack or bread. Based on the survey, this company does have not a method in raw material inventory planning that can minimize inventory cost. This research aims to analyze the application of MRP method on raw material inventory and its effect on inventory cost efficiency. MRP is a method to determine the amount and timing of raw materials available in the production process. This research was conducted at Ganep's Bakery Solo. The technique used in this research is Lot Sizing with Lot for Lot calculation method, Economic Order Quantity, and Part Period Balancing. From the calculation the cost of inventory issued by the company in one year is Rp 40.000.000,00. The results obtained from the MRP calculation using Lot for Lot is Rp 40.000.000,00, Economic Order Quantity is Rp 27.357.780,00and Part Period Balancing method is Rp36.566.900,00. Calculation of MRP with Lot Sizing technique using EOQ method resulted in the smallest inventory costRp 27.357.780,00. Using MRP method can minimize the inventory cost Â±68,39% of the inventory cost applied by the company.Keywords: Material Requirement Planning, Lot for Lot, Economic Order Quantity, Part Period Balancing